2010
DOI: 10.1212/wnl.0b013e3181d8fff4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of insurance status on migraine care in the United States

Abstract: The uninsured, and those with Medicaid, receive substandard therapy for migraine, at least in part because they receive more care in emergency departments and less in physicians' offices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 20 publications
1
27
0
2
Order By: Relevance
“…EHR databases-such as the one being built and maintained by OCHIN-will be key to the study of how health reform policies implemented under the Patient Protection and Affordable Care Act of 2010 (PPACA) affect the uninsured and underinsured. [41][42][43][44][45][46][47][48][49] Although some states are putting considerable resources toward building all-payer claims databases to better address the PPA-CA's evaluation requirements, 50 such databases will not include uninsured and transiently insured populations. Information from EHR data will be more accurate than administrative claims data; thus, it is imperative to further develop and validate important EHR data resources and to evaluate the extent to which EHR data can be used to supplement (or substitute for) claims data.…”
Section: Research and Policy Implicationsmentioning
confidence: 99%
“…EHR databases-such as the one being built and maintained by OCHIN-will be key to the study of how health reform policies implemented under the Patient Protection and Affordable Care Act of 2010 (PPACA) affect the uninsured and underinsured. [41][42][43][44][45][46][47][48][49] Although some states are putting considerable resources toward building all-payer claims databases to better address the PPA-CA's evaluation requirements, 50 such databases will not include uninsured and transiently insured populations. Information from EHR data will be more accurate than administrative claims data; thus, it is imperative to further develop and validate important EHR data resources and to evaluate the extent to which EHR data can be used to supplement (or substitute for) claims data.…”
Section: Research and Policy Implicationsmentioning
confidence: 99%
“…7 Medicaid patients were less likely than privately insured patients to receive abortive (OR 1.6, 95% CI 1.1-2.3) and prophylactic therapy (OR 1.5, 95% CI 1.0-2.1) for migraine headaches in a national study of more than 68 million visits for migraine. 6 By contrast, a study of the Medical Expenditure Panel Survey using the National Health Interview Survey found people with epilepsy had similar medical resource utilization but lower out-of-pocket costs for antiepileptic drugs compared to those with private insurance. 23 Poststroke care may also differ between Medicaid and privately insured neurologic patients.…”
Section: Discussionmentioning
confidence: 95%
“…There are several challenges to headache care among those on Medicaid, underinsured, or uninsured. One study, which analyzed 11 years of data from the National Ambulatory Medical Care Survey and National Hospital Ambulatory Medical Care Survey from 1997 to 2007, showed that the uninsured and those with Medicaid receive substandard therapy for migraine, at least in part because they received less care in physicians’ offices and more care in EDs . Transportation to specialized headache care centers poses a problem as headache clinics are few, and in some states headache specialty centers do not exist .…”
Section: Introductionmentioning
confidence: 99%
“…One study, which analyzed 11 years of data from the National Ambulatory Medical Care Survey and National Hospital Ambulatory Medical Care Survey from 1997 to 2007, showed that the uninsured and those with Medicaid receive substandard therapy for migraine, at least in part because they received less care in physicians' offices and more care in EDs. 22 Transportation to specialized headache care centers poses a problem as headache clinics are few, and in some states headache specialty centers do not exist. 23 Individuals with lower incomes may not have the time, financial, social, or other resources for coordinated headache care, especially if it includes long-distance travel or an inpatient headache stay (childrearing, work loss, etc).…”
Section: Introductionmentioning
confidence: 99%